Introduction: Posthumanism and Media Studies - Wilde, Poppy; IV, J.J. Sylvia (Journal of Posthumanism, 2024)
Posthumanism fosters a more inclusive and less hierarchical approach to our entanglements with both human and non-human elements. Posthuman theory, particularly as articulated by N. Katherine Hayles and Rosi Braidotti, has long been influential in media and cultural studies. Ferrando (2020) argues: posthuman ethics invites us to follow on three related layers. First of all, as a post-humanism, it marks a shift: from universalism to perspectivism, from multiculturalism to pluralism and diversity. As a postanthropocentrism, it induces a change of strategy: from human agency to agential networks, from technology to eco-technology. As a postdualism, it requires an evolution of our awareness: from individuality to relationality, from theory to praxis. (147) This Special Issue of the Journal of Posthumanism therefore asks, how does such posthuman perspectivism, pluralism, agentiality, eco-technology, relationality, and praxis, apply to the future of media and cultural studies? How might we understand the very concept of future?